The impact of organizational culture on corporate financial performance: a review - Hussein Ali, Hosni S.; Mohd Said, Ridzwana; Abdullah, Amalina; Mat Daud, Zaidi (IJECM, 2017)
The effect of organizational culture on corporate financial performance has been an interesting field of research over the years. The jury is still out on whether the organizational culture affects the corporate financial performance, or not. Organizational culture has been found to be a major factor for organizational success. The purpose of this paper is to review the impact of organizational culture on corporate financial performance. Empirical studies were reviewed and summarized. This review concludes that the relationship between organizational culture and corporate financial performance is inconclusive. In consequence, further investigations are necessary.